2016
DOI: 10.1007/s11357-016-9915-0
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in motor unit firing pattern of vastus lateralis muscle during low-moderate contraction

Abstract: Age-related changes in motor unit activation properties remain unclear for locomotor muscles such as quadriceps muscles, although these muscles are preferentially atrophied with aging and play important roles in daily living movements. The present study investigated and compared detailed motor unit firing characteristics for the vastus lateralis muscle during isometric contraction at low to moderate force levels in the elderly and young. Fourteen healthy elderly men and 15 healthy young men performed isometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 54 publications
5
83
0
2
Order By: Relevance
“…Muscle weakening and atrophy begin in the fourth decade of life with a rate of strength loss of approximately 1% per year, and accelerates in the later decades [3]. To date, a significant body of research has identified structural and morphological alterations in the muscles and the nervous system [4,5] that are all likely associated with the aging-related decline in neuromuscular functions, such as muscle weakness and reduced postural performance [6][7][8][9]. These age-dependent structural changes are known to be preceded by a loss of preferably highly myelinated axons that are the neuronal components of high threshold motor units (for review see [5,10]).…”
Section: Introductionmentioning
confidence: 99%
“…Muscle weakening and atrophy begin in the fourth decade of life with a rate of strength loss of approximately 1% per year, and accelerates in the later decades [3]. To date, a significant body of research has identified structural and morphological alterations in the muscles and the nervous system [4,5] that are all likely associated with the aging-related decline in neuromuscular functions, such as muscle weakness and reduced postural performance [6][7][8][9]. These age-dependent structural changes are known to be preceded by a loss of preferably highly myelinated axons that are the neuronal components of high threshold motor units (for review see [5,10]).…”
Section: Introductionmentioning
confidence: 99%
“…Through the use of an array of electrodes rather than the usual bipolar configuration, a more accurate decomposition of the EMG signal appears to be feasible and it has shown promising results with regards to neural drive and motor unit properties estimation. Only few studies that used high-density EMG have been performed on elderly adults [166,167]. They reported evidence of impaired motor unit discharge characteristics which indicates a reduced integrity of the motor unit firing modulation [165,166].…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies that used high-density EMG have been performed on elderly adults [166,167]. They reported evidence of impaired motor unit discharge characteristics which indicates a reduced integrity of the motor unit firing modulation [165,166]. Developing this technique could be key to more extensively interpreting the neural and intrinsic changes occurring with ageing.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus necessary to identify some particularly desirable food components and develop them in AFF food items for application to QOL improvement ( Figure 3). A number of papers have already been published [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69].…”
Section: S I P: Cross-ministerial Strategic Innovation Promotion Progmentioning
confidence: 99%